Reflections on Regional Integration and Food Security in Developing Sub-Saharan African Countries - (:unkn) unknown (My University, 2024)
Regional integration holds significant potential for Africa, a vast continent with over 1.2 billion people. This study investigates the complex relationship between regional integration and food security in developing Sub-Saharan African countries. Key agreements include the Economic Commission for Africa, which supports initiatives such as the Economic Community of West African States (ECOWAS), the Common Market for Eastern and Southern Africa (COMESA), the Economic Community of Central African States (ECCAS), and the Southern African Development Community (SADC). Despite the potential of regional integration to address food security challenges, significant gaps in understanding and implementation persist. Identify and analyse key areas requiring further research to leverage regional integration for improved food security outcomes fully. The study employs a comprehensive literature review and analysis of empirical evidence to examine several critical gaps. These include the impact of regional trade agreements on smallholder farmers, the effectiveness of cross-border food security initiatives in conflict-prone areas, and challenges in harmonizing food safety standards. Furthermore, it investigates the implementation challenges of regional food reserve systems, the impact of currency fluctuations on food affordability, and the potential of regional value chains to improve food security. The study addresses the role of informal cross-border trade, the impact of regional infrastructure projects, and the alignment of national agricultural policies with regional integration goals. Additionally, we examine the effectiveness of regional mechanisms for addressing transboundary diseases and the impact of labour mobility on agricultural productivity. Findings reveal that while regional integration offers significant potential for enhancing food security, its benefits are not fully realized due to various factors, including policy inconsistencies, infrastructure
Keywords: African Research